PENGARUH FREKUENSI PEMUPUKAN BIO URIN DENGAN PENAMBAHAN ZPT ORGANIK SEBAGAI PUPUK DAUN PADA RUMPUT ODOT (Pennisetum purpureum CV. Mott) TERHADAP KANDUNGAN LEMAK KASAR, SERAT KASAR DAN BAHAN EKSTRAK TANPA NITROGEN - Nurullah H A Rena; Badat Muwakhid; M. Farid Wadjdi (Dinamika Rekasatwa: Jurnal Ilmiah (e-Journal), 2019)
This research aims to know the values of the coarse fiber (SK), the fat rude (LK) and Extract Without Nitrogen in grass Odot. The material used in this research is the grass odot. The method of this research is to experiment with a random Design complete (RAL) Factorial pattern 3 x 3 orthogonal, each repeated three times as much. factors in use i.e. spraying frequency and dose bio urine. Todose 5% done spraying 1 time, to 10% in dose do spraying twice and for doses 15% done spraying 3 times plus control without spraying frequency and dose bio urine. Data results obtained were analyzed (ANOVA) range two way if any real influence continued with the smallest Real Difference Test (BNT). From the results of the analysis of the influence of the menunjukkn variety is evident (P <0.01) against the value of the fat content of coarse, BETN and influential real (P < 0.05) for Rough fiber. Value rataan LK, SK and BETN each range (2.46%-3.51%), (20,67-27,88%), (46,74-53,85). Value control rataan LK, SK and BETN (2.22, 28.50, 42.35). So in this study it can be concluded that thetreatment of spraying frequency and dose bio urine on grass odot is very influential to the quality content of grass odotKeywords: bio of urine spraying frequency, grass odot, LK, SK, and BETN